Gender and GDP Contributions: The Effects of Culture - Graham, Elizabeth (My University, 2008)
This paper uses Ordinary Least Squares regressions to examine the cultural, demographic, and geographical sources of differences in the Gross Domestic Product (GDP) contributions of women. These cultural variables include religion, level of female education, fertility, political representation, and the mean age of marriage. The results show that culture has considerable explanatory power for female labor force participation rates, the gender wage gap, and women?s contributions to GDP. Surprisingly, fertility rates were not found to have any impact on women?s contributions to GDP.
Oshkosh Scholar, Volume 3, 2008 pp. 16-25.
Keywords: Women in culture and society; Female labor force; Gross national product--Econometric models.; Gross Domestic Product; Women -- economic conditions; Women -- Employment